Framing Analysis of G20 Bali Summit Coverage on Online Media CNNINDONESIA.Com and Metrotvnews.Com - Nurul Khairunnisa Saragi (Indonesian Journal of Communication and Social, 2024)
G20 Bali Summit the seventeenth meeting of the Group of Twenty (G20). The summit has been held in Bali, Indonesia, in 2022. The Indonesian Presidency runs from December 1, 2021 until the summit in the fourth quarter of 2022. This study aims to find out how online media CNNIndonesia.com and Metrotvnews.com framing their news of the G20 Bali Summit news. Through framing analysis, you can see and process information to shape the perspective of Indonesian people on the same event in the online media. This study used qualitative methods using Robert Entman's framing model analysis. The framing analysis method carried out was to analyze 10 news items in the two online media about the activities of the G20 Bali Summit. This news analysis was carried out with four measuring tools of the Robert N. Entman model, namely define problem, diagnose problem, make moral judgment, and treatment recommendation. The results of the study concluded that online media CNNIndonesia.com and Metrotvnews.com have carried out moral judgment, namely discussing economic recovery in crisis due to the Covid-19 pandemic so that President Joko Widodo in his opening speech at the G20 Bali Summit invited all G20 heads of state to work together in the success of this activity in order to restore the economy.